2010
DOI: 10.1103/physrevb.82.235115
|View full text |Cite
|
Sign up to set email alerts
|

Localization of correlated fermions in optical lattices with speckle disorder

Abstract: Strongly correlated fermions in three-and two-dimensional optical lattices with experimentally realistic speckle disorder are investigated. We extend and apply the statistical dynamical mean-field theory, which treats local correlations non-perturbatively, to incorporate on-site and hopping-type randomness on equal footing. Localization due to disorder is detected via the probability distribution function of the local density of states. We obtain a complete paramagnetic ground state phase diagram for experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 65 publications
2
24
1
Order By: Relevance
“…The additional prediction that increasing disorder can also drive delocalization, when applied to a strongly correlated MI state [162,163] still needs to be verified experimentally, since probing transport properties in the Mott regime is more challenging. Also note that, strictly speaking, a true MI does not exist for unbounded Speckle disorder in the thermodynamic limit [164]. Remarkably, the experiment [166] observed that disorder-induced localization persists also at finite temperature, which could be an indication of MBL, which we discuss in the following.…”
Section: Disorder and Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional prediction that increasing disorder can also drive delocalization, when applied to a strongly correlated MI state [162,163] still needs to be verified experimentally, since probing transport properties in the Mott regime is more challenging. Also note that, strictly speaking, a true MI does not exist for unbounded Speckle disorder in the thermodynamic limit [164]. Remarkably, the experiment [166] observed that disorder-induced localization persists also at finite temperature, which could be an indication of MBL, which we discuss in the following.…”
Section: Disorder and Localizationmentioning
confidence: 99%
“…It vanishes at the transition, in contrast to the arithmetically averaged or global density of states, which remains finite in the Anderson insulator. These studies were later extended to the full statistical DMFT, where a self-consistent distribution of the LDOS is determined [163], also taking into account experimentally realistic Speckle-type disorder [164]. AF correlations have also been included within DMFT+TMT [165], leading to the magnetic phase diagram in figure 14.…”
Section: Disorder and Localizationmentioning
confidence: 99%
“…The Hubbard Hamiltonian is one of the most relevant models for investigating strongly correlated systems in condensed matter theory, of both bosonic as well as fermionic nature [19][20][21][22][23]. In this article we study the characteristics of an interacting ultracold Fermi gas exposed to periodic modulations of the optical lattice strength.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To overcome these limitations, DMFT was extended to describe spatially nonuniform systems, in approaches sometimes called "Statistical DMFT" [5][6][7][8][9][10][11][12][13][14][15][16] (some authors call the same approach "Real-Space DMFT" [17][18][19] ). Here, the local DMFT order parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%